2021
DOI: 10.1021/acs.jafc.0c07782
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Herbicidal Activity of Triketone-Aminopyridines as Potent p-Hydroxyphenylpyruvate Dioxygenase Inhibitors

Abstract: Exploring novel p-hydroxyphenylpyruvate dioxygenase (EC 1.13.11.27, HPPD) inhibitors has become one of the most promising research directions in herbicide innovation. On the basis of our tremendous interest in exploiting more powerful HPPD inhibitors, we designed a family of benzyl-containing triketone-aminopyridines via a structure-based drug design (SBDD) strategy and then synthesized them. Among these prepared derivatives, the best active 3-hydroxy-2-(3,5,6-trichloro-4-((4-isopropylbenzyl)­amino)­picolinoyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…The solvation free energy (Δ G solv ) could be divided into electrostatic solvation free energy (Δ G GB ) and a nonpolar solvation free energy (Δ G np ). Furthermore, the entropic contribution was calculated following the previous work. , On the other hand, the decompose module was used to perform energy decomposition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The solvation free energy (Δ G solv ) could be divided into electrostatic solvation free energy (Δ G GB ) and a nonpolar solvation free energy (Δ G np ). Furthermore, the entropic contribution was calculated following the previous work. , On the other hand, the decompose module was used to perform energy decomposition.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the entropic contribution was calculated following the previous work. 42,43 On the other hand, the decompose module was used to perform energy decomposition. QM/MM Calculations.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…A rational design approach based on molecular hybridization and structure-based ligand design was applied to generate additional new classes of triketone-aminopyridines as inhibitors of HPPD activity (Figure 8). 25 In the first step of design, a preliminary hit compound was generated by merging the triketone system with the tetra-substituted pyridine ring of picloram (a broad-spectrum herbicide of the auxin class). In the second step of design, molecular docking simulations suggested that the primary amino group of the hit compound could be decorated with hydrophobic appendages that were predicted to be accommodated within a hydrophobic pocket delimited by Phe392, Leu369, and Met335.…”
Section: ■ Decoration Of Minimum Common Pharmacophoric Motif To Overc...mentioning
confidence: 99%
“…As selective herbicides, 4-hydroxyphenylpyruvate dioxygenase (HPPD) inhibitors have attracted extensive attention because they have a unique bleaching mode of action. These inhibitors can block the homergy of tyrosine by inhibiting the efficacy of the HPPD enzyme, which is an iron-tyrosinate protein participating in the catabolism of tyrosine, leading to carotenoid deficiency and eventually resulting in the death of plants after presenting with the unique bleaching symptom. , Commercial HPPD inhibitors are generally classified into three broad categories (Figure ), including pyrazoles, triketones, and isoxazoles. Their common substructure is 2-benzoylethen-1-ol, which can closely chelate the ferrous ion in the active center of the HPPD enzyme to competitively inhibit the binding of p -hydroxyphenylpyruvic acid (HPPA) to ferrous ions. Although the 2-benzoylethen-1-ol substructure can serve as the bioisostere of phenylpyruvic acid, its conservatism makes some weeds gradually develop resistance to HPPD inhibitors. , Currently, it is urgent to further diversify the substructure of HPPD inhibitors to delay the development of resistance.…”
Section: Introductionmentioning
confidence: 99%